2023
DOI: 10.3390/nano13061023
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of PVDF–TiO2 Mixed-Matrix Membrane with PVP and PEG as Pore-Forming Agents for BSA Rejection

Abstract: Polymeric membranes offer straightforward modification methods that make industry scaling affordable and easy; however, these materials are hydrophobic, prone to fouling, and vulnerable to extreme operating conditions. Various attempts were made in this study to fix the challenges in using polymeric membranes and create mixed-matrix membrane (MMMs) with improved properties and hydrophilicity by adding titanium dioxide (TiO2) and pore-forming agents to hydrophobic polyvinylidene fluoride (PVDF). The PVDF mixed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Li reported that when the casting solution contained PEG 200 additive the resulting membrane was thermodynamically less stable than those produced with PEG 400 and PEG 600 9 . Amirilargani and Mohammadi found that, when the molecular weight of PEG increased from 400 to 1500 and 6000 Da, increasing numbers of macrovoids and larger finger‐like pores occurred in the membrane 10–12 . But Lee indicated that the membrane pore structure mainly depended on the concentration of PEG 13 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Li reported that when the casting solution contained PEG 200 additive the resulting membrane was thermodynamically less stable than those produced with PEG 400 and PEG 600 9 . Amirilargani and Mohammadi found that, when the molecular weight of PEG increased from 400 to 1500 and 6000 Da, increasing numbers of macrovoids and larger finger‐like pores occurred in the membrane 10–12 . But Lee indicated that the membrane pore structure mainly depended on the concentration of PEG 13 …”
Section: Introductionmentioning
confidence: 99%
“…PEG, as an additive in the casting solution, plays an important role as a pore formation agent 7–11 . Li reported that when the casting solution contained PEG 200 additive the resulting membrane was thermodynamically less stable than those produced with PEG 400 and PEG 600 9 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 It was established that the permeability of PPSU composite membrane and porosity, hydrophobicity and fouling resistance were increased with PEG addition to the casting solution. 33,34 In addition, the hydrophilic nature of PEG influences the solvent and non-solvent exchange rate during the phase-inversion process and it has a great influence on the pore size, pore distribution and filtration flux. 35 In the current research, a PPSU composite membrane was prepared using the phase-inversion process.…”
Section: Introductionmentioning
confidence: 99%